From macrocyclic to linear and further: naturally degradable polyesters from the fungus Ascotricha sp. ZJ-M-5. Issue 32 (11th August 2016) - Zhang, Jin-Ling; Wang, Wen-Jing; Xu, Xiu-Mei; Li, Dan-Yi; Hua, Hui-Ming; Ma, En-Long; Li, Zhan-Lin
Abstract: Four new polyketide-derived polyesters, including three linear ones ascotrichesters A–C (1 –3 ) and one macrocyclic ascotrichalactone A (4 ), and the known biosynthetic building blocks (−)-orthosporin (7 ) and (−)-6-hydroxymellein (8 ), were isolated from the still culture product of the fungus Ascotricha sp. ZJ-M-5 in Czapek Dox broth without Mg 2+, along with a new hexaketide orthosporinin (5 ) and its visible light-catalyzed [2+2] dimerized derivative diorthosporinin (6 ). HPLC monitoring of the stability of4 in H2 O disclosed the fact that macrocyclic lactone4, with a unreported motif for polyesters, 2, 4-dihydroxy-6-(4-hydroxy-2-oxopentyl)benzoic acid, is the natural precursor which undergoes hydrolysis followed by intramolecular lactonization at pH 7 or 8 to yield the linear polyester3 and parallel reactions to afford5 . This result demonstrated that the previously proposed biosynthetic pathway for polyesters from linear to cyclic should be reversed. Additionally, the growth inhibitory effects of1 –8 against two human leukemia cancer cell lines and the antibacterial activities of compounds3 and4 were assessed. Graphical abstract: